1996
DOI: 10.1088/0964-1726/5/6/002
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical modelling of residual and transformational stresses in SMA composites

Abstract: SMA composites are a class of smart materials in which shape memory alloy (SMA) actuators are embedded in a polymer matrix composite. The difference in thermal expansion between the SMA and the host material leads to residual stresses during processing. Similarly, the SMA transformations from martensite to austenite, or the reverse, also generate stresses. These stresses acting in combination can lead to SMA/epoxy interfacial debonding or microcracking of the composite phase. In this study the residual and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In a later work the same authors (Boyd and Lagoudas, 1996b) have reported that by proper selection of the manufacturing process, namely, by proper pre-straining of the SMA fibers in the martensitic phase, a two-way composite SME is possible even though the fibers exhibit only one-way SME. Berman and White (1996) have studied the effect of the phase transformation of SMA wires embedded in a polymer matrix on the development of residual stresses. It has been found that by properly designing the SMA composite system, the residual stresses can be controlled or totally eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…In a later work the same authors (Boyd and Lagoudas, 1996b) have reported that by proper selection of the manufacturing process, namely, by proper pre-straining of the SMA fibers in the martensitic phase, a two-way composite SME is possible even though the fibers exhibit only one-way SME. Berman and White (1996) have studied the effect of the phase transformation of SMA wires embedded in a polymer matrix on the development of residual stresses. It has been found that by properly designing the SMA composite system, the residual stresses can be controlled or totally eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…The lattice-invariant shear mechanism accommodates the different shape of the new martensite within the transformed austenite. The uniqueness of shape memory lies in the fact that the latticeinvariant shear step of this transformation occurs almost solely by twinning [14,15]. Twinning forces the BCC shape into a monoclinic phase with no volumetric change and no broken bonds.…”
Section: Shape Memory Effect Of Sma Fiber By Applied Load and Temperamentioning
confidence: 99%
“…Stimuli-sensitive materials cover a broad spectrum of materials that respond to external fields such as pH, temperature, and electric/magnetic field [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] . These materials show promise in applications ranging from pumps and valves, to shock tube instrumentation.…”
Section: Stimuli Sensitive Materials (Ssm)mentioning
confidence: 99%